The buried foundation of the Gilgamesh epic : the Akkadian Huwawa narrative - Fleming, Daniel E. (Cuneiform Monographs, 2010)
The Akkadian Gilgamesh Epic, perhaps the most famous of Mesopotamian literature, has been considered the artistry of one author inspired by Sumerian tales. Specialists have assumed that all the earliest evidence (ca. 1800-1700 BCE) reflects this creative unity. Deep contrasts in characterization and narrative logic, however, distinguish the central adventure to defeat the monster Huwawa from what precedes and follows it. The Huwawa narrative stands on its own, so that the epic must have been composed from this prior Akkadian composition. Recognition of the tale embedded in the epic allows each block of material to be understood on its own terms. Such literary-historical investigation from contemporary texts is new to Assyriology and may produce important results when applied to other Mesopotamian writing. \'The book is well written and tightly argued...This makes it a first point of reference for anyone interested in the OB evidence for the Gilgamesh Epic.\' Scott C. Jones, Covenant College